2013
DOI: 10.1080/1553118x.2013.777903
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment-Education and Strategic Communication: A Case Study of Sesame Workshop's “Talk, Listen, Connect” Initiative for Military Families

Abstract: The Sesame Street Talk, Listen, Connect (TLC) initiative is a multimedia example of Entertainment-Education that leveraged the popular Sesame Street platform to deliver key information to military families about how to communicate with children about feelings related to deployment and homecomings, and other tough issues related to military life. This paper is organized as an in-depth case study of the TLC initiative, including interviews with key program developers. The research analyzes the TLC initiative as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…More than 80% of families reported that the program helped cope with the stress of deployment and parental separation (Nolan & Misca, 2018;Wright et al, 2013). A case study by Desens & Hughes (2013) found that the Talk, Listen, Connect 'Entertainment-Education' model is particularly effective as a type of strategic communication. The resource is easily accessible outside the US; Kudler & Porter (2013, p. 177) report that the program has reached hundreds of thousands of households around the world through free DVDs and related materials as well as direct downloads from the Sesame Street website.…”
Section: Other Us Programs and Resourcesmentioning
confidence: 99%
“…More than 80% of families reported that the program helped cope with the stress of deployment and parental separation (Nolan & Misca, 2018;Wright et al, 2013). A case study by Desens & Hughes (2013) found that the Talk, Listen, Connect 'Entertainment-Education' model is particularly effective as a type of strategic communication. The resource is easily accessible outside the US; Kudler & Porter (2013, p. 177) report that the program has reached hundreds of thousands of households around the world through free DVDs and related materials as well as direct downloads from the Sesame Street website.…”
Section: Other Us Programs and Resourcesmentioning
confidence: 99%